« Conforter une école bienveillante et exigeante » : représentations, préoccupations et pratiques déclarées - Éric Saillot (Université de Provence, 2018)
Caring school has been institutionally emerging in France since the school refoundation Law (2013). This text presents the main results of a survey realized in 2016 in the academy of Caen in Normandy. This study aims at describing and understanding school professionals' representations, concerns and self-reported practice, thanks to 418 full questionnaires. This text will finally take a critical look at caring and demanding school.